2021
DOI: 10.1111/pbi.13604
|View full text |Cite
|
Sign up to set email alerts
|

The MYB family transcription factor TuODORANT1 from Triticum urartu and the homolog TaODORANT1 from Triticum aestivum inhibit seed storage protein synthesis in wheat

Abstract: Summary Seed storage proteins (SSPs) are determinants of wheat end‐product quality. SSP synthesis is mainly regulated at the transcriptional level. Few transcriptional regulators of SSP synthesis have been identified in wheat and this study aims to identify novel SSP gene regulators. Here, the R2R3 MYB transcription factor TuODORANT1 from Triticum urartu was found to be preferentially expressed in the developing endosperm during grain filling. In common wheat (Triticum aestivum) overexpressing TuODORANT1, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 71 publications
1
13
0
Order By: Relevance
“…The multinucleate endosperm stage is associated with endosperm proliferation and cell differentiation, and the early and maximum grain filling stages corresponding to storage accumulation. According to the similar grain morphology, endosperm at 1–5 DPA of T. urartu were in the multinucleate endosperm stage; endosperm at 6–10 DPA, 11–15 DPA and 16–20 DPA were in the early, maximum and late grain filling stages, respectively; and endosperm at 21–25 DPA were in the desiccation stage (Luo et al., 2021).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The multinucleate endosperm stage is associated with endosperm proliferation and cell differentiation, and the early and maximum grain filling stages corresponding to storage accumulation. According to the similar grain morphology, endosperm at 1–5 DPA of T. urartu were in the multinucleate endosperm stage; endosperm at 6–10 DPA, 11–15 DPA and 16–20 DPA were in the early, maximum and late grain filling stages, respectively; and endosperm at 21–25 DPA were in the desiccation stage (Luo et al., 2021).…”
Section: Resultsmentioning
confidence: 97%
“…To investigate transcriptome dynamics in endosperm development, endosperm samples (with the embryo, aleurone, seed coat and pericarp removed) from the genome‐sequenced T. urartu accession PI 428198 at 5, 10, 15, 20 and 25 days post‐anthesis (DPAs) were used in the RNA‐Seq analysis (Luo et al., 2021). Grain development in common wheat includes five main stages: fertilization (0 DPA); multinucleate endosperm (1–5 DPA); cellularization and early grain filling (6–13 DPA); maximum grain filling (14–28 DPA); and desiccation (25–38 DPA; Kaushik et al., 2020; Shewry, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…4 B, Table S 4 ). A previous study showed that TaODORANT1 participates in seed storage protein synthesis in wheat [ 44 ]. Our results showed that its promoter has several SNPs in Zhou8425B compared to CS (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, TaGAMyb regulates glutenin gene expression by directly binding to a 5′-C/TAACAAA/C-3′-like motif in the promoter of HMW-GS genes and by recruiting GCN5 to modulate histone acetylation [ 20 ]. Additionally, the MYB TFs TuODORANT1 and TaODORANT1 are suppressors of SSP synthesis [ 21 ]. An NAC family TF (i.e., storage protein repressor; SPR) binds to the cis -element 5′-CANNTG-3′ to suppress the accumulation of SSPs [ 22 ].…”
Section: Introductionmentioning
confidence: 99%